2015
DOI: 10.1371/journal.pone.0141934
|View full text |Cite
|
Sign up to set email alerts
|

DNA Packaging Specificity of Bacteriophage N15 with an Excursion into the Genetics of a Cohesive End Mismatch

Abstract: During DNA replication by the λ-like bacteriophages, immature concatemeric DNA is produced by rolling circle replication. The concatemers are processed into mature chromosomes with cohesive ends, and packaged into prohead shells, during virion assembly. Cohesive ends are generated by the viral enzyme terminase, which introduces staggered nicks at cos, an approx. 200 bp-long sequence containing subsites cosQ, cosN and cosB. Interactions of cos subsites of immature concatemeric DNA with terminase orchestrate DNA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
1
1
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 68 publications
(98 reference statements)
0
1
0
Order By: Relevance
“…The order of subsites is R3-I1-R2-R1, where R2 is oriented opposite to R3 and R1. An exception is phage N15, the cosB of which consists of a single R sequence, R3-N15, analogous in location to R3-λ [19,20] (Figures 1C and 2).…”
Section: Terminase:cos-λ Interactionsmentioning
confidence: 99%
See 3 more Smart Citations
“…The order of subsites is R3-I1-R2-R1, where R2 is oriented opposite to R3 and R1. An exception is phage N15, the cosB of which consists of a single R sequence, R3-N15, analogous in location to R3-λ [19,20] (Figures 1C and 2).…”
Section: Terminase:cos-λ Interactionsmentioning
confidence: 99%
“…The Rpps in the Rpp-TerS complexes are proposed to bind specifically to R3-PICI sites. Given the absence of I1, R2, and R1 sequences, PICIs cosBs architecture resembles cosB-N15, which contains only an R3 equivalent [19,20]. Interestingly, the putative R3 sequences of cos-PICI-A and cos-PICI-C differ in just a few positions.…”
Section: The Pici Cosmentioning
confidence: 99%
See 2 more Smart Citations
“…Their structural and packing proteins are also highly analogous, making it likely that N15 DNA packing follows a pathway similar to that of lambda [1]. It has even been demonstrated that the N15 specific terminase can package lambda DNA with reasonable efficiency [41].…”
Section: Lytic Replicationmentioning
confidence: 99%